2023
DOI: 10.1101/2023.02.24.529904
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activity-dependent induction of astrocytic Slc22a3 regulates sensory processing through histone serotonylation

Abstract: Neuronal activity drives global alterations in gene expression within neurons, yet how it directs transcriptional and epigenomic changes in neighboring astrocytes in functioning circuits is unknown. Here we show that neuronal activity induces widespread transcriptional upregulation and downregulation in astrocytes, highlighted by the identification of a neuromodulator transporter Slc22a3 as an activity-inducible astrocyte gene regulating sensory processing in the olfactory bulb. Loss of astrocytic Slc22a3 redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…In addition to its role as a neuromodulator, 5-HT was previously shown to be capable of forming covalent bonds with certain substrate proteins via transamidation by the tissue Transglutaminase 2 enzyme, a process referred to as serotonylation (17). In more recent studies, our group identified a new class of histone posttranslational modification (PTM) termed monoaminylation, whereby monoamine neurotransmitters, such as 5-HT, dopamine and histamine, can be transamidated onto histone glutamine residues (18)(19)(20)(21)(22)(23). We showed that histone H3 glutamine (Q) 5 is a primary site for these PTMs and demonstrated that H3 monoaminylation states play important roles in the regulation of neuronal transcriptional programs, both during early development/cellular differentiation and in adult brain.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its role as a neuromodulator, 5-HT was previously shown to be capable of forming covalent bonds with certain substrate proteins via transamidation by the tissue Transglutaminase 2 enzyme, a process referred to as serotonylation (17). In more recent studies, our group identified a new class of histone posttranslational modification (PTM) termed monoaminylation, whereby monoamine neurotransmitters, such as 5-HT, dopamine and histamine, can be transamidated onto histone glutamine residues (18)(19)(20)(21)(22)(23). We showed that histone H3 glutamine (Q) 5 is a primary site for these PTMs and demonstrated that H3 monoaminylation states play important roles in the regulation of neuronal transcriptional programs, both during early development/cellular differentiation and in adult brain.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of unique transcriptomic profiles of astrocytes highlight several intriguing possibilities, including functional specializations within known astrocyte function 75,80,81 . Furthermore, the number of unique genes between ASTs outnumbered the shared ones, which indicates potentially uniquely specialized astrocyte cell types 76,82,83 . For example, AST4 possesses a unique transcriptome with a small overlap with other ASTs, and GO terms suggest that this subtype could be linked to functions in the neuro-vascular unit 80 .…”
Section: Discussionmentioning
confidence: 99%
“…At this site, H3 serotonylation epigenetically regulates transcription either alone or in combination with the neighboring lysine 4 tri-methylation (K4me3) PTM to enhance permissive gene expression through interactions with reader proteins 33 . The combinatorial H3K4me3Q5ser PTM has been detected in regions throughout the adult brain, where it coordinates relevant gene expression programs upstream of neural differentiation and contributes to sensory processing and stress-induced behavioral plasticity in adult brain, demonstrating diverse roles for this PTM across various functional domains 34,35 . Moreover, the presence of histone serotonylation in heart, testes and other mouse organs suggest additional actions in peripheral tissues 24 .…”
Section: Introductionmentioning
confidence: 99%